Weakly Gorenstein comodules over triangular matrix coalgebras - Dingguo Wang; Chenyang Liu; Xuerong Fu (AIMS Mathematics, 2022)
In this paper, we characterise weakly Gorenstein injective and weakly Gorenstein coflat comodules over triangular matrix coalgebras by introducing the class of weakly compatible bicomodules. In particular, Gorenstein injective and Gorenstein coflat comodules are investigated.